1998
DOI: 10.1183/09031936.98.11010144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral hyposensitization with recombinant Der f2 on immediate airway constriction in a murine allergic model

Abstract: Recombinant Der f2 (rDer f2) has recently been developed as a promising allergen for the diagnosis and immunotherapy of house-dust mite allergy, and studies in immunology. The aim of the present study was to evaluate whether oral administration of rDer f2 could suppress an immediate allergic reaction in mice sensitized with mite allergen. We developed a murine allergic model that showed bronchoconstriction after inhalation of rDer f2, and studied the effect of oral administration of rDer f2 on the reaction.Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The Th1/ Th2 imbalance are correlated with the changes in serum total IgE and IgG, allergen-specific serum IgE and IgG levels, airway responsiveness and eosinophilia. Thus, in the present study, we suggested that AHR improvement is associated with a regulation in Th1/Th2 balance, a decrease in allergen-specific serum IgE and an increase in allergen-specific serum IgG in the allergic model of rats with oral immunotherapy, which is consistent with previous study, indicating that oral hyposensitization with recombinant Der f2 attenuates immediate airway constriction in a murine allergic model [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The Th1/ Th2 imbalance are correlated with the changes in serum total IgE and IgG, allergen-specific serum IgE and IgG levels, airway responsiveness and eosinophilia. Thus, in the present study, we suggested that AHR improvement is associated with a regulation in Th1/Th2 balance, a decrease in allergen-specific serum IgE and an increase in allergen-specific serum IgG in the allergic model of rats with oral immunotherapy, which is consistent with previous study, indicating that oral hyposensitization with recombinant Der f2 attenuates immediate airway constriction in a murine allergic model [22].…”
Section: Discussionsupporting
confidence: 92%
“…The conventionally used allergens include house mite allergen [19][20][21][22], pollen extract [23,24], ovalbumin [25] and peanut protein [26], Many studies showed that oral administration of allergen, including recombinant Derf2, effectively suppresses IgE responses in the allergic model of mice [19,20]. Although we supposed that the effects of Derfdrop is antigen-specific and it is not likely that Derfdrop affects immune response via antigen-non-specific way, it is still necessary to set up the experiments to verify the specificity of Derf allergen by using other allergen-induced asthmatic animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning a mite allergic model, Hsiue et al [4] recently reported the induction of allergic airway inflammation in guinea pigs that showed severe eosinophilia of the airway and immediate bronchoconstriction after intravenous injection of crude mite extract [4]. We have also developed murine allergic models exhibiting immediate airway constriction or neutrophil influx into the airway after antigen inhalation by using rDer f 2 as a sensitizing and provoking antigen [21,22]. However, no reports on the induction of anti-mite IgE in primates have been published to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most experimental allergic asthma models have been developed by systemic sensitization that involves either intraperitoneal or subcutaneous injection with adjuvants, such as aluminum hydroxide. Some investigators have developed mouse models of allergic airway eosinophilia (Ichinose et al, 2003;Sadakane et al, 2002;Yu et al, 1999), allergen-induced AHR (Herz et al, 1996), or allergen-induced airway obstruction (Yasue et al, 1998) using only local exposure of mite allergen without adjuvant. The intent of such models is to mimic the route of sensitization in humans as closely as possible.…”
Section: Introductionmentioning
confidence: 99%